LINKAGES BETWEEN MANAGEMENT PERFORMANCE AND SUSTAINABILITY OF COMMUNAL WWTP IN JAKARTA - Haley Tanjung, Fadly
SANIMAS-IsDB Program was initiated by Ministry of Public Works in 2015 and Jakarta Provincial Government had joined to build Communal WWTP in 23 locations until 2018. Bappenas (2018) showed that 96% water body in Jakarta has been highly polluted and according to Said (2008), 75% contributions of that number comes from domestic wastewater and makes environmental conditions in Jakarta as Indonesia’s capital is very worrying about. Several Communal WWTP sustainability indicators i.e stakeholders’ participation and operational costs (Brix, dkk., 2011; Rande, 2017). Whilst the management performance of all 23 Communal WWTP have never been assessed. Even though the improvement of management performance is important to assure its sustainability (Ulum, dkk., 2015; Molinos-Senante, dkk., 2016). For that reason, a research which study lingkages between management performance and sustainability in Jakarta is needed. JICA study (2012) showed that 60% of existing 35 WWTP in Jakarta currently not operating, so the purpose of this research is formulated to identify linkages between management performance and sustainability of Communal WWTP in Jakarta. Several research targets are as follows: identifying sustainability conditions, assessing management performance of existing 23 Communal WWTP, and formulating lingkages between management performance and sustainability. Methods of analysis that used in this research in quantitative. For the first target, multicriteria analysis is used which started by literature study and weighting indicators using Analytical Hierarchy Process (AHP). Second target using multicriteria analysis based on indicators by Ministry of Public Works. Third target using association/correlational analysis with Rho Spearman’s test to examine linkages between management performance and sustainability. The conclusion of this research is management performance has a linear relationship, but weak to its sustainability. This means that the higher the performance of Communal WWTP management, the higher the sustainability, and vice versa.